Hak Memilih Bagi Anggota Tentara Nasional Indonesia: Studi Komparasi Hak Memilih Anggota Angkatan Bersenjata di Beberapa Negara - Sugeng, Adjdam Riyange Zulfachmi (UI Scholars Hub, 2021)
The right to vote is the characteristic of democracy, which is to elect representatives who make, amend, and repeal a law. Without that right, there is no form of transfer of power from people to the government. But in practice, there are restrictions on that right, that is limitation of the right to vote on active members of Indonesian National Armed Forces (TNI). Type of legal research is normative juridical, comparison of law and legal history. The basis for this regulation of right to vote for members of TNI is maintaining the neutrality of TNI. While there are several forms of regulation of the right to vote for members of the armed forces, namely by giving full right, giving the right partially, and not giving the right, and making arrangements through two ways, namely listed on constitution or listed on law that is not constitution, like statute.